Arabica Coffee Agribusiness Development Strategy in The Tegal Subur Farmers Group Tegalmulyo Village Kemalang District Klaten Regency - Oki, Nurahman; Mahananto; Norbertus Citra, Irawan (Journal of Rural and Urban Community Studies, 2025)
Arabica coffee is one of the leading plantation commodities in Tegalmulyo Village, Kemalang District, Klaten Regency. Tegal Subur Farmers Group is one of the active farmer groups in Tegalmulyo Village that manages the cultivation and post harvest of arabica coffee. Studies on the strategy for developing arabica coffee agribusiness by farmer groups are still limited, especially in the Klaten area. The purpose of this research was to determine the internal and external factors that influence the development of Arabica coffee agribusiness in the Tegal Subur Farmers Group and to formulate alternative strategies for developing arabica coffee agribusiness in the Tegal Subur Farmers Group, Tegalmulyo Village, Kemalang District, Klaten Regency. This research is a descriptive qualitative research with primary and secondary data. Determination of respondents by census with a total of 24 members of the Tegal Subur Farmers Group. The analysis tools used include the IFE and EFE Matrices, the IE Matrix and the SWOT Matrix. The results showed that the total score of the IFE Matrix was 2,913, while the total score of the EFE Matrix was 2,886. Analysis of the strategic position with the IE Matrix shows that the strategic position is in cell V, namely the area of implementation of the strategy of maintaining and preserving. Internal and external factors analyzed use SWOT Matrix, produces 11 alternative strategies. The right alternative strategy to be implemented for the development of arabica coffee agribusiness in the Tegal Subur Farmers Group is that the farmer group completes PIRT on the packaging of ground coffee products.